Laser Tattoo Removal: A New Tool for Hospital-based Violence Prevention?. Issue 10 (1st November 2020) - Foran, Christopher P.; Clark, Damon H.; Alling, Torey; Meza Sanchez, Irene; Fischer, Briah; Henry, Reynold; Matsushima, Kazuhide; Inaba, Kenji; Demetriades, Demetrios G.
Introduction: Gang-related tattoos may increase an individual's risk for violent victimization. We present our early experience using a physician-staffed tattoo removal initiative as 1 component of a violence prevention program. Methods: Surgeons from our trauma department in partnership with a community advocacy group performed voluntary laser tattoo removal for individuals within our catchment area. Clients were asked to complete a voluntary, anonymous survey. This survey addressed tattoo acquisition, identified motives and goals for tattoo removal, and reported if those goals were met by the tattoo removal service. Issues involving gang affiliation and interpersonal violence were specifically queried. Results are listed as simple percentages. Results: 81 of 122 (66%) program enrollees completed the survey. The average number of laser removal sessions at the time of questionnaire was 3 (range 1-15). 41% of respondents possessed gang or "crew" related tattoos. 22% of respondents possessed a tattoo related to an intimate partner who was gang affiliated. 21% of respondents desired tattoo removal for the motive of leaving gang affiliation with 94% of those respondents reporting success. 59% of respondents sought tattoo removal to improve employment opportunities with 81% of those respondents reporting success. 30% of respondents desired tattoo removal to improve personal safety or avoid violence with 80% of those respondents reporting success. Conclusion: Stated client goals for tattoo removal and their subjective reports of success achieving these goals demonstrate the possible effectiveness of laser tattoo removal as a tool to help clients avoid future violence and progress toward gang disengagement. Trauma departments should consider laser tattoo removal as part of future violence prevention initiatives.